Use of Caenorhabditis elegans as a model to study Alzheimer’s disease and other neurodegenerative diseases - Alexander, Adanna G.; Marfil, Vanessa; Li, Chris (Frontiers in Genetics, 2014)
Advances in research and technology has increased our quality of life, allowed us to combat diseases, and achieve increased longevity. Unfortunately, increased longevity is accompanied by a rise in the incidences of age-related diseases such as Alzheimer’s disease (AD). AD is the sixth leading cause of death, and one of the leading causes of dementia amongst the aged population in the USA. It is a progressive neurodegenerative disorder, characterized by the prevalence of extracellular Aβ plaques and intracellular neurofibrillary tangles, derived from the proteolysis of the amyloid precursor protein (APP) and the microtubule-associated protein tau, respectively. Despite years of extensive research, the molecular mechanisms that underlie the pathology of AD remain unclear. Model organisms, such as the nematode, Caenorhabditis elegans, present a complementary approach to addressing these questions. C. elegans has many advantages as a model system to study AD and other neurodegenerative diseases. Like their mammalian counterparts, they have complex biochemical pathways, most of which are conserved. Genes in which mutations are correlated with AD have orthologues in C. elegans, including an APP ortholog, APL-1, a tau homolog, PTL-1, and presenilin homologues, such as SEL-12 and HOP-1. Since the neuronal connectivity in C. elegans has already been established, C. elegans is also advantageous in modeling learning and memory impairments seen during AD. This article addresses the insights C. elegans provide in studying AD and other neurodegenerative diseases. Additionally, we explore the advantages and drawbacks associated with using this model.